Arterial hypertension and stroke primary prevention - O. D. Ostroumova; N. L. Rolik; K. A. Ishchenko (Кардиоваскулярная терапия и профилактика, 2005)
Literature data on essential arterial hypertension role in stroke pathogenesis are reviewed. Antihypertensive therapy potential in risk reduction of acute stroke is demonstrated. The roles of various drug classes in primary stroke prevention are compared.